ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NO.93/PUU-X/2012 TERHADAP PENYELESAIAN SENGKETA PERBANKAN SYARIAH DI INDONESIA - GALA PERDANA PUTRA (PREMISE LAW JURNAL, 2015)
The result of the research showed that first, The Constitutional Court, in its Ruling No. 93/PUU-X/2012 only consents to a part of it by stating that the explanation of Article 55, paragraph 2 of Law No. 21/2008 on Sharia Banking is contrary to the 1945 Constitution and nonbinding; secondly, legal consequence after the Ruling of the Constitutional Court No. 93/PUU-X/2012 is the selection of the dispute settlement forum in a non-litigation which is not only found in the explanation of Article 55, paragraph 2 of Law No, 21/2008 on Sharia Banking, but which is also used in settling the dispute such as consultation, negotiation, reconciliation, non-banking mediation, experts’ opinion, and so on, as long as it is agreed by the conflicting parties. Specifically, the authority of District Court in hearing sharia banking dispute is declared void; and thirdly, Religious Court is actually prepared in settling sharia banking dispute since has had preparedness in legal provisions and regulations in supporting its Ruling. The Religious Administrative of Justice, Bank Indonesia, the Supreme Court, and Judicial Commission consistently perform regular training, either domestically or abroad for the judges of Religious Court throughout Indonesia in order to improve the quality of Religious Court judges in understanding sharia jurisprudence and economy and the execution of Religious Court’s Ruling. People do not need to worry about the enforcement/authority of Religious Court since it has the same as the District Court in carrying out the execution of the Ruling, either through its bailiffs or through the police. It is recommended that Article 55 of Law No. 21/2008 on Sharia Banking should be revised so that there will be no overlapping authority which causes legal uncertainty. Those who are involved in sharia banking, sharia banks, clients, and notaries who make sharia financial deeds should select and use Religious Court as the settlement forum when there is a dispute after there is no agreement after negotiation has been held between the conflicting parties. Keywords: Sharia Banking, Forum Selection, Ruling of the Constitutional Court, Religious Court